2021
DOI: 10.3389/fonc.2021.617289
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Validation of a Prognostic Model for Cancer Dependency Genes Based on CRISPR-Cas9 in Gastric Adenocarcinoma

Abstract: As a CRISPR-Cas9-based tool to help scientists to investigate gene functions, Cancer Dependency Map genes (CDMs) include an enormous series of loss-of-function screens based on genome-scale RNAi. These genes participate in regulating survival and growth of tumor cells, which suggests their potential as novel therapeutic targets for malignant tumors. By far, studies on the roles of CDMs in gastric adenocarcinoma (GA) are scarce and only a small fraction of CDMs have been investigated. In the present study, data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
(49 reference statements)
2
23
0
Order By: Relevance
“…In contrast, genes with expression that related positively to the signature’s risk score were significantly enriched in the invasion, metastasis, and immune biological processes ( Figure 4 ). Among the 10 survival-related genes included in the signature, the risk-associated genes PWP2 and TGFB1 have been suggested to be associated with GC invasion and metastasis ( 50 , 51 ), and ZBTB7A , a protection-associated gene, plays a tumor-suppressive role in GC cells ( 52 ). METTL2B was found to be RNA methyltransferases and play important roles in tumorigenesis ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, genes with expression that related positively to the signature’s risk score were significantly enriched in the invasion, metastasis, and immune biological processes ( Figure 4 ). Among the 10 survival-related genes included in the signature, the risk-associated genes PWP2 and TGFB1 have been suggested to be associated with GC invasion and metastasis ( 50 , 51 ), and ZBTB7A , a protection-associated gene, plays a tumor-suppressive role in GC cells ( 52 ). METTL2B was found to be RNA methyltransferases and play important roles in tumorigenesis ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ORCs in BC The ORCs was involved in the malignant progression of multiple tumors. Studies had shown that ORCs were differentially expressed in colorectal cancer, gastric cancer, and lung cancer and were related to biological behaviors such as cell proliferation, migration, and invasion [12][13][14][15][16]19 . Based on the Oncomine database, we also found that at least one of the ORCs was differentially expressed in colorectal cancer, gastric cancer, lung cancer and other tumors.…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, a large amount of evidence have shown that ORC is involved in other biological processes, such as heterochromatin formation, cytokinesis, viral replication, DNA damage repair, cognitive impairment and radiation in ammatory response [4][5][6][7][8][9] . ORCs are also differentially expressed in a number of tumors, such as gliomas 10 , endometrial cancer 11 , colon cancer [12][13][14] , gastric cancer 15,16 , liver cancer 17 , esophageal cancer 18 , and lung cancer 19 . They are implicated in diverse biological processes, including cell proliferation, migration, invasion, tumor stem cell maintenance, and chemotherapy resistance [11][12][13][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other four genes of GlycoSig have not been investigated in the context of CRC; however, many studies have indicated their significance in other cancer types. Previous studies have shown that ALG8 could be a variate of prognostic model for gastric adenocarcinoma (51) and frequently amplified hotspot on 11q14.1 (ALG8) associated with significantly worse prognosis for breast cancer (52). The ALG6 single-nucleotide polymorphism (SNP) is a potential prognostic biomarker for cutaneous melanoma and is likely through modulating gene expression (53).…”
Section: Discussionmentioning
confidence: 99%